2019
DOI: 10.1080/13670050.2019.1600470
|View full text |Cite
|
Sign up to set email alerts
|

Resemiotisation from page to stage: translanguaging and the trajectory of a musilingual youth’s poem

Abstract: This article reports on part of an ethnographic research project undertaken over a period of 20 months in Leeds, UK, with a youth spoken word (YSW) poetry organisation. The research focused on the fluid practices in which the youth engage that span spoken, written, visual, gestural, digital, musical and spatial modes, and across times and places. Given its inherent fluidities, YSW is a particularly interesting practice for studying semiosis. Among other aspects, the research focused on the trajectories of poem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…According to these authors: "Affective scholarship has induced focus on how writing not merely seeks to transport lived affects from the field onto paper, but how it aims to evoke a sense of these affects in the reader." In some cases, we are also able to reconstruct part of what Kell (2009Kell ( , 2015 refers to as the trajectories of the poems (see also Bradley and Moore, 2018;Moore and Bradley, 2019), by identifying poetic resources, themes or ideas that travel across workshop activities.…”
Section: Methodsmentioning
confidence: 99%
“…According to these authors: "Affective scholarship has induced focus on how writing not merely seeks to transport lived affects from the field onto paper, but how it aims to evoke a sense of these affects in the reader." In some cases, we are also able to reconstruct part of what Kell (2009Kell ( , 2015 refers to as the trajectories of the poems (see also Bradley and Moore, 2018;Moore and Bradley, 2019), by identifying poetic resources, themes or ideas that travel across workshop activities.…”
Section: Methodsmentioning
confidence: 99%
“…From a methodological perspective, five studies have followed ethnographic (qualitative) methods in this session (KANG et al, 2017;AXELROD;COLE, 2018;DURÁN, 2020a;KARLSSON et al, 2019a;MOORE;BRADLEY, 2020). Three have used qualitative approaches with a focus on The study showed that a translanguaging space supported and strengthened students' scientific meaning-making processes.…”
Section: Studies Focusing On Written and Oral Productionmentioning
confidence: 99%
“…(AXELROD;COLE, 2018;KANG;SWANSON;BAULER, 2017;LEONET;CENOZ; GORTER, 2020a;MOORE;BRADLEY, 2020;OMIDIRE;AYOB, 2020).Furthermore, looking at research from TP focusing on written and oral production, five studies demonstrated the researchers used a range of writing tasks with peer interactions (COADY; MAKALELA; LOPEZ, 2019a; DURÁN, 2020b; HIDALGO; LÁZARO-IBARROLA, 2020b; KARLSSON; NYGÅRD LARSSON; JAKOBSSON, 2019b; MARTIN-BELTRÁN; CHEN; GUZMAN, 2018). Additionally, it is noteworthy that those studies have been developed not just in language classes in bilingual education but also in diverse educational and theoretical contexts such as Content and Language Integrated Learning (CLIL) (PARRA; PROCTOR, 2021b; Xabier; LASAGABASTER, 2019b), task repetition (HIDALGO; LÁZARO-IBARROLA, 2020b), Science classes…”
mentioning
confidence: 99%
“…In Emilee's recent work (e.g. Moore & Bradley, 2020), part of the Translation and Translanguaging: Investigating Linguistic and Cultural Transformations in Superdiverse Wards in Four UK Cities (TLANG) project, she has also used the notion of translanguaging as a way to talk about multimodality, or communicative resources beyond spoken and written language. In our work as researchers and teacher educators, and also as mothers and grandmother, we have been witness to how people, and children and young people in particular, communicate both through and beyond spoken and written codes, to incorporate semiotic resources that are not strictly linguistic: gesture, ways of dressing, references to mass media, dance moves, etc.…”
Section: Our Research and Teacher Education Practicementioning
confidence: 99%